Soil Health Status Under Different Positions of Damota Subwatershed, East Hararghe Zone, Ethiopia - Teferi Taddesse Woldemariam; Bobe Bedadi; Lemma Wogi; Kebede Woldetsadik; Amare Bantider (Applied and Environmental Soil Science)
The study evaluated the soil health conditions in Damota Subwatershed in 2023, assessing the physical and chemical characteristics of the soils to provide information that could be used to support sustainable agricultural practices and environmental protection efforts. In line with this, 36 composite soil samples were collected from 12 mapping units at three slope and altitudinal positions and analyzed in a laboratory to understand soil health status, identifying three textural classes: sandy clay loam, sandy loam, and loamy sand. Soil bulk densities ranged from 1.35 to 1.68 gm cm−3, slightly above threshold, while total porosity ranged from 36.60% to 49.06% below the optimal range. The available water capacity of the soils ranged from 66.5 to 185.1 mm·m−1. In relation with the chemical properties of the soils, the pH-H2O (in 1:2.5 soil to water) of the soils ranged from 7.58 in mapping unit 11 to 8.76 in mapping unit 4. The SOC and TN levels for all mapping units in the three subwatershed positions were classified as very low to low. The soils’ phosphorus content ranged from 3.53 mg·kg−1 in the USWS to 9.08 mg·kg−1 in the LSWS positions within mapping units 11 and 6, respectively. The levels of exchangeable calcium, magnesium, and potassium varied from high to very high, with the exception of sodium, which was found to be low. The CEC of the soils also ranged from medium to high (14.35 and 43.95 cmol(+) kg−1). Iron availability varied from very low to low, manganese from low to high, copper from low to high, and zinc from medium to high. Low SOC, TN, and AP levels in different slope classes indicate poor soil health status, adversely impacting sustainable agriculture. The study has significant implications for sustainable land use, circular agriculture, and evidence-based policy creation at individual subwatershed scales.